Complications of Robotic Surgery in Oncological Gynecology: The Experience of the Brazilian National Institute of Cancer - Érico Lustosa Ferreira; Julio C Nunes; Mariana Zandoná; Caio Perret; Rossano Fiorelli; Agostinho Manuel da Silva Ascenção (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
The number of surgeries performed with robotic equipment has increased ever since its release by the Food and Drug Administration (FDA) in 2005 [1].  Robotic surgery is well accepted and seems to be as effective as laparoscopy in the treatment of endometrial and cervix cancers [2,3]. Some of the advantages of using this method over the traditional laparoscopic technique include 3D visualization, tremor filtration, greater dexterity, better ergonomics, lower blood loss and lower post-operative pain index [4].